Kaplan (Himmelfarb), Rose (audio interview #1 of 1) - Kaplan (Himmelfarb), Rose (b. 1896 - d. unknown); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - Rose Kaplan (Himmelfarb) was interviewed in her home in Petaluma. Her husband was present for most of the interview and occasionally she turned to him to elaborate. Kaplan was referred to the Feminist History Research Project as one of the women living in the radical Jewish community of egg ranchers in Petaluma, California. Because she lived in North California, a second interview with her became impractical, and as a result this single interview does not go beyond early 1940, when we moved to California. TOPICS - family background and economic status; work in the Ukraine; religion; Ukrainian community; progroms; immigration experiences; 1908 strike in Ukraine; living conditions, New York; garment work, New York; working conditions; wages and hours; ILGWU, Local 9; WTUL; 1916 strike; and left-wing split in the union;abolition of women's branches, ILGWU Locals; 1921 election of left-wing organizers; 1922 national convention and expulsion of left-wing Locals; internal struggles between right and left-wing factions; 1926 special convention for reconciliation; general strike for forty-hour work week; formation of Needle Trades Industrial Union; Depression; dissolution of Local 9; CP membership; cooperative living; Joint Action Committee, San Francisco,1925; Unemployed Councils, NY; working conditions, 1930s; resurgence of left-wing movement; and move to California; 3/13/1975